Digital Adaptation and Perceptions of Architecture and Interior Design Students on Online Lecture Methods - Tita Cardiah; Andiyan Andiyan; Husna Izzati; Eliyana Firmansyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The COVID-19 pandemic has had a significant impact on education, especially learning methods that must be carried out online. The online learning method also applies to Architecture and Interior Design students in the planning and design studio lecture activities, which were initially carried out offline in the studio and now have to be carried out online from their respective homes. Various obstacles faced in architectural and interior planning and design studio lectures require students to adapt virtually and digitally. Visually and digitally, there are many limitations, both from using technological devices to the facilities owned by lecturers and students. The study used a qualitative descriptive method, searching for data through questionnaires with the respondents being students of architecture and interior design. The study results found that the adaptation of online lectures is not only a virtual and digital problem but includes physical and non-physical problems. Virtual and digital transformations affect the process and quality of learning outcomes for architectural and interior planning and design studio courses. Physical adaptation requires supporting facilities in the form of tools and equipment to assist studio lectures. Non-physically is an adaptation to changes in time, patterns and methodologies of learning, behaviour, psychology, and the internet network. Behavioural and psychological adaptations and perceptions need more in-depth research in future studies.